2021
DOI: 10.1002/cfp2.1127
|View full text |Cite
|
Sign up to set email alerts
|

Understanding consumer's adoption of financial robo‐advisors at the outbreak of the COVID‐19 crisis in Malaysia

Abstract: The COVID‐19 crisis that resulted in diminished close contact interaction and increased financial volatility could influence consumer's perception toward online automated financial robo‐advisor, in order to manage their financial planning. Based on the data collected (i.e., between February [9 reported cases] and March [36 reported cases] 2020) within the developed urban cities in Malaysia just before the nationwide lockdown, the present study examines the antecedents of financial robo‐advisor's adoption durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…Part of this growth may be attributed to the fact the ease and usefulness of robo-advisors has a positive influence on attitudes towards and adoption of the technology (Belanche et al, 2019). In fact, there is a large body of research that has examined why consumers are willing to adopt robo-advisors (see Hentzen et al, 2021 for a review) across a range of countries including Germany (Seiler and Fanenbruck, 2021), Pakistan (Wang et al, 2021), Malaysia (Gan et al, 2021) and USA (Fan, 2021). However, recent research (Zhang et al, 2021) has suggested consumers prefer human advisers with high expertise over robo-advisors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of this growth may be attributed to the fact the ease and usefulness of robo-advisors has a positive influence on attitudes towards and adoption of the technology (Belanche et al, 2019). In fact, there is a large body of research that has examined why consumers are willing to adopt robo-advisors (see Hentzen et al, 2021 for a review) across a range of countries including Germany (Seiler and Fanenbruck, 2021), Pakistan (Wang et al, 2021), Malaysia (Gan et al, 2021) and USA (Fan, 2021). However, recent research (Zhang et al, 2021) has suggested consumers prefer human advisers with high expertise over robo-advisors.…”
Section: Introductionmentioning
confidence: 99%
“…, 2021 for a review) across a range of countries including Germany (Seiler and Fanenbruck, 2021), Pakistan (Wang et al. , 2021), Malaysia (Gan et al. , 2021) and USA (Fan, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…nature. com/33anbt1) 64 Thiam M.E.B., Liu J., Aston J 2019 Organizational ethics focus—professional ethics is integrated within the banking culture 66 San-Jose L., Cuesta J 2018 Organizational ethics focus—Islamic banks 67 Lenz S., Neckel S 2019 Organizational ethics focus—ethical banks between moral self-commitment and economic expansion 71 Bowers B., Boyd N., Mcgoun E 2020 Sustainability management—banks engaging in green washing for looking better 76 Usher E 2020 Supervision and regulation—principles for Responsible Banking 77 Phuong N.A 2020 Sustainability strategies—bank green banking adoption 78 Diener F., Špa?ek M 2020 Sustainability strategy—sustainable reporting 79 Karkowska R 2019 Sustainability management—concept of sustainable banks—business models 82 Fenwick M., Vermeulen E.P.M 2020 Supervision and regulation—to establish an environment for successful and sustainable “ecosystems”, regulators need to become active participants in these more open forms of business organization 83 Valls Martínez M.C., Martín-Cervantes P.A., Peña Rodríguez S 2021 Sustainability strategy—ethical banking business model 88 Bukhari S.A.A., Hashim F., Amran A …”
Section: Appendix 1: Sample Database - 103 Articlesmentioning
confidence: 99%
“…It was considered in relation to the technology and the ICT-enabled service provider (Dutot, 2015;Sinha & Mukherjee, 2016). Research by Gan et al (2021) and Lourenco et al (2020) shows that trust in robo-advisory positively influences the intention to take automated financial advice. This factor is particularly relevant for consumers with little investment experience, little amount of savings, and a low level of risk tolerance (Jung et al, 2018).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%